Method for Deriving Functional Architectures from Use Cases. Issue 2 (23rd May 2013) - Lamm, Jesko G.; Weilkiens, Tim
ABSTRACT Functional architecture enables the description of systems independent of their technology. A method for obtaining functional architectures for systems (the FAS method) is introduced. It provides a well‐defined procedure for deriving functional architecture from use cases by using heuristics for grouping functions and allocating them to functional blocks. A specialty of the FAS method is the structural representation of functional architectures in block‐oriented form. An example system from the hearing instrument domain is used for demonstrating the method. The application of the FAS method together with the SysML modeling language is described, and modeling tool support is discussed. The authors report their experiences with the method from industrial projects, for example that analysts and architects could improve their communication by means of the FAS method. It is concluded that the method together with tool support facilitates the team process of creating model‐based functional architectures based on use cases.